Analyzing Speech Acts in Gritte Agatha's Podcast: 'Jadi Korban Bullying Satu Sekolah, Karena Peran Cinderella' - Nurjannah, Nurjannah; Saerudin, Sahur (Saree: Research in Gender Studies, 2024)
ABSTRACT ENGLISH:Podcasts are an interesting type of YouTube content to discuss because there are numerous variations of speech acts in conversations between speakers and their speech partners. The goal of this study is to describe speech acts using locution, illocution, and perlocution from the Gritte Agatha Podcast "Jadi Korban Bullying Satu Sekolah, karena Peran Cinderella". This study's data consists of oral statements or utterances made during a conversation between Gritte Agatha, the host, and Ricky, the speaker. This study takes a qualitative descriptive approach. The data collection technique is the listening method, followed by the note-taking technique, which involves recording relevant speech data in accordance with the research's target and purpose. The data analysis technique used qualitative descriptive techniques and pragmatic analysis to describe and categorize speech acts in the Gritte Agatha Podcast. The results revealed that this podcast contained three types of speech acts: locutionary, illocutionary, and perlocutionary speech acts. Locution speech acts include news sentences, question sentences, and command sentences. The only speech acts found in illocutionary speech are assertive, directive, and expressive. In this study, only one type of perlocutionary speech act was identified: forcing the interlocutor to do something.   ABSTRACT INDONESIAN:Podcast merupakan salah satu jenis konten YouTube yang menarik untuk dibahas karena terdapat banyak variasi tindak tutur dalam percakapan antara penutur dan mitra tuturnya. Tujuan penelitian ini adalah untuk mendeskripsikan tindak tutur yang menggunakan tindak tutur lokusi, ilokusi, dan perlokusi dari Podcast Gritte Agatha “Jadi Korban Bullying Satu Sekolah, karena Peran Cinderella”. Data penelitian ini berupa pernyataan atau ujaran lisan yang dibuat selama percakapan antara Gritte Agatha sebagai pembawa acara dan Ricky sebagai narasumber. Teknik analisis data menggunakan teknik deskriptif kualitatif dan analisis pragmatik untuk mendeskripsikan dan mengategorikan tindak tutur dalam Podcast Gritte Agatha. Teknik pengumpulan data yang digunakan adalah menyimak dan mencatat data tuturan yang relevan sesuai dengan tujuan penelitian. Hasil penelitian menunjukkan bahwa podcast ini mengandung tiga jenis tindak tutur, yaitu tindak tutur lokusi, ilokusi, dan perlokusi. Tindak tutur lokusi meliputi kalimat berita, kalimat tanya, dan kalimat perintah. Tindak tutur yang ditemukan dalam tuturan ilokusi hanya tindak tutur asertif, direktif, dan ekspresif. Dalam penelitian ini, hanya satu jenis tindak tutur perlokusi yang diidentifikasi: memaksa lawan tutur untuk melakukan sesuatu.